Investigation of wearable health tracker version updates. Issue 1 (9th October 2019) - Woolley, Sandra I; Collins, Tim; Mitchell, James; Fredericks, David
Abstract : Background: Wearable fitness trackers are increasingly used in healthcare applications; however, the frequent updating of these devices is at odds with traditional medical device practices. Objective: Our objective was to explore the nature and frequency of wearable tracker updates recorded in device changelogs, to reveal the chronology of updates and to estimate the intervals where algorithm updates could impact device validations. Method: Updates for devices meeting selection criteria (that included their use in clinical trials) were independently labelled by four researchers according to simple function and specificity schema. Results: Device manufacturers have diverse approaches to update reporting and changelog practice. Visual representations of device changelogs reveal the nature and chronology of device iterations. 13% of update items were unspecified and 32% possibly affected validations with as few as 5 days between updates that may affect validation. Conclusion: Manufacturers could aid researchers and health professionals by providing more informative device update changelogs.